2013
DOI: 10.1038/ismej.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

You are what you talk: quorum sensing induces individual morphologies and cell division modes in Dinoroseobacter shibae

Abstract: Dinoroseobacter shibae, a member of the Roseobacter clade abundant in marine environments, is characterized by a pronounced pleomorphism. Cell shapes range from variable-sized ovoid rods to long filaments with a high copy number of chromosomes. Time-lapse microscopy shows cells dividing either by binary fission or by budding from the cell poles. Here we demonstrate that this morphological heterogeneity is induced by quorum sensing (QS). D. shibae utilizes three acylated homoserine lactone (AHL) synthases (luxI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(126 citation statements)
references
References 66 publications
7
119
0
Order By: Relevance
“…Further, the authors of this study convincingly demonstrated that the phenotype of a luxI1 mutant could be restored by the addition of the corresponding C 18 -HSL at saturating concentrations. Additional transcriptome analyses in the background of this deletion mutant further supported the hypothesis of the AIdependent morphological cell variability (25).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Osupporting
confidence: 58%
See 1 more Smart Citation
“…Further, the authors of this study convincingly demonstrated that the phenotype of a luxI1 mutant could be restored by the addition of the corresponding C 18 -HSL at saturating concentrations. Additional transcriptome analyses in the background of this deletion mutant further supported the hypothesis of the AIdependent morphological cell variability (25).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Osupporting
confidence: 58%
“…Another interesting aspect of AI-linked heterogeneity was recently identified in the alphaproteobacterium Dinoroseobacter shibae (25). D. shibae is a member of the Roseobacter clade, which is highly abundant in marine habitats (26).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Omentioning
confidence: 99%
“…Recently we found that knock-out of the autoinducer synthase luxI 1 led to a reduced expression of ctrA , cckA , chpT, divL as well as the QS genes luxR 2 I 2 and the AHL synthase luxI 3 during exponential growth and stationary phase, resulting in a complete loss of autoinducer biosynthesis [27]. Here, we found that the latter QS genes were also down-regulated in the CtrA phosphorelay mutants in both growth phases (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…are also known to possess multiple systems and signals ( Table 2). The QS signals modulating these QSS range from unsubstituted-to substituted-HSLs, as well as peptides (DKPs), quinolones, hormones [69,[94][95][96][97][98][99][100][101][102][103][104][105]. In Yersinia, luxI/R homologues are majorly regulated by substituted AHLs [106][107][108].…”
Section: Othersmentioning
confidence: 99%